Abrocitinib may improve itch and quality of life in patients with itch‐dominant atopic dermatitis - Jonathan I. Silverberg; Jacob P. Thyssen; Irina Lazariciu; Daniela E. Myers; Erman Güler; Raj Chovatiya (Wiley, 2024)
Abstract Background Patients with atopic dermatitis (AD) exhibit heterogeneous clinical phenotypes, reflecting different combinations of itch and lesional severity. AD with severe itch but clear‐moderate lesions, also known as itch‐dominant AD, is a common clinical phenotype. Objectives To evaluate abrocitinib efficacy in patients with moderate‐to‐severe AD who have itch‐dominant AD. Methods This post hoc analysis includes pooled data from clinical trials of patients with moderate‐to‐severe AD receiving abrocitinib (100 or 200 mg) as monotherapy (phase 2b; phase 3 JADE MONO‐1 and JADE MONO‐2) or in combination with topical therapy (phase 3 JADE COMPARE). Data from the ongoing long‐term JADE EXTEND trial (data cutoff April 2020) were also evaluated. Itch‐dominant AD was defined as baseline Peak Pruritus Numerical Rating Scale (PP‐NRS) score of 7−10 and Investigator's Global Assessment of 0−3 or Eczema Area and Severity Index of 0‒21. Assessments included a ≥4‐point improvement in PP‐NRS (PP‐NRS4), PP‐NRS score of 0 (no itch) or 1 (little itch) in patients with PP‐NRS score ≥2 at baseline, ≥4‐point improvement from baseline in Patient‐Oriented Eczema Measure (POEM‐4), Patient Global Assessment (PtGA) of clear or almost clear, and Dermatology Life Quality Index (DLQI) score of 0 or 1 (no impact or little impact of AD on quality of life [QoL]). Results In the pooled monotherapy trials, 37% of patients had itch‐dominant AD at baseline. As early as Week 2, more patients with itch‐dominant AD achieved PP‐NRS4 with abrocitinib 100 mg (35%) and abrocitinib 200 mg (57%) versus placebo (7%); 6% and 22% versus 0%, respectively, achieved PP‐NRS 0/1. More patients achieved a PtGA of clear/almost clear at Week 12 with abrocitinib 100 mg (28%) and abrocitinib 200 mg (45%) than placebo (9%). Additionally, abrocitinib led to clinically meaningful improvements in POEM and DLQI. Most patients with itch‐dominant AD experienced itch improvement over time with abrocitinib monotherapy or with concomitant topical therapy; 86%-87% and 62%-67% of patients had no itch‐moderate itch and clear‐moderate lesions by weeks 24 and 48, respectively. Conclusions Abrocitinib is highly efficacious in patients with itch‐dominant AD, demonstrating rapid, deep, and sustained improvements in itch and clinically meaningful improvements in patients' QoL. Trial Registration Numbers NCT02780167; NCT03349060; NCT03575871; NCT03720470; NCT03422822.